Respiratory support during the surgical treatment of tracheal scar stenosis n patients with thyroid pathology - V.V. Boyko; V.V. Kritsak; A.L. Sochnieva; V.V. Tkachenko (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Currently, surgical interventions on the chest and respiratory tract have undergone significant progress. New methods of performing complex resections and reconstructions of the respiratory tract are increasingly being introduced into practice. Regenerative medicine is developing — from the use of cadaveric transplants to modern biosynthetic respiratory tracts. In this regard, knowledge and skills in using various special respiratory techniques are necessary. The purpose of the work was to study the methods of respiratory support in tracheal surgery from the standpoint of patient safety, surgical comfort and intraoperative interaction between the surgeon and anesthesiologist. Materials and methods. The study included 130 patients with stenosing diseases of trachea and main bronchi on the background of thyroid pathology who were operated on in the Institute’s clinic since 2017 using flow apnoeic oxygenation at the stages of resection and reconstruction of the respiratory tract. The average age of the patients was 39 ± 12 years, the physical status according to the classification of the American Society of Anesthesiologists corresponded to classes I–II. Flow apnoeic oxygenation was used at the main stages of circular tracheal resection with anastomosis, tracheoplasty with the placement of a T-shaped tube, separation of the tracheoesophageal fistula with circular tracheal resection, two-level circular tracheal resection, and other tracheoplastic operations. Results. The advantages of flow apnoeic oxygenation in terms of surgical comfort were immobility of the lungs and airways, absence of spraying of tracheobronchial secretions and blood from the surgical wound, and prevention of complications associated with impaired airway patency during surgical manipulations, which can be complicated by lung barotrauma. Respiratory support for resection and reconstruction of the airways in patients with thyroid diseases can be performed using flow apnoeic oxygenation. Conclusions. The flow apnoeic oxygenation technique allows avoiding serious complications associated with respiratory support inherent in other techniques. The choice of technology is determined by the level and type of lesion, the degree of stenosis, the length of the affected area, and the characteristics of the surgical approach.